2000
DOI: 10.1007/s003350010142
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of human PREB; a gene that maps to a genomic region associated with trisomy 2p syndrome

Abstract: We have isolated the human homolog of a novel rodent gene that may be involved in the regulation of pituitary gene transcription. The human PREB gene encodes a predicted protein of 417 amino acids, exhibiting several sequences characteristic of the WD-motif protein family. PREB transcripts were detected in every human fetal and adult tissue examined, although a great variation in levels of expression was observed. PREB was mapped to human Chromosome 2p23, a region of the genome associated with partial trisomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…While we have shown that mSec12 is a Sar1‐specific exchange factor, other functions for mSec12 may exist. During our cloning and characterization of mouse mSec12, nearly identical (> 99%) rat and human homologs of mSec12 were identified as a putative prolactin regulatory element binding (PREB) transcription factor (19,27). PREB has been characterized as a ubiquitously expressed protein that is highly abundant in tissues that are active in secretion (liver, pancreas, pituitary).…”
Section: Discussionmentioning
confidence: 99%
“…While we have shown that mSec12 is a Sar1‐specific exchange factor, other functions for mSec12 may exist. During our cloning and characterization of mouse mSec12, nearly identical (> 99%) rat and human homologs of mSec12 were identified as a putative prolactin regulatory element binding (PREB) transcription factor (19,27). PREB has been characterized as a ubiquitously expressed protein that is highly abundant in tissues that are active in secretion (liver, pancreas, pituitary).…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA sequence of the human Sec12/PREB gene has previously been reported [34]. However, nucleotide cytidine-186 is thymidine in their sequence and this alters the deduced amino acid sequence from a leucine to a phenylalanine at residue 19.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ORF reported here differs by the inclusion of an inserted glycine-136 residue. Glycine-136 is conserved in the human and rat homologues [29,34]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations